Cross-training effect of chronic whole-body vibration exercise: a randomized controlled study. (2nd April 2020) - Aydın, Tuğba; Kesiktaş, Fatma Nur; Baskent, Akın; Karan, Ayşe; Karacan, Ilhan; Türker, Kemal S.
Abstract: Purpose: To determine whether unilateral leg whole-body vibration (WBV) strength training induces strength gain in the untrained contralateral leg muscle. The secondary aim was to determine the potential role of spinal neurological mechanisms regarding the effect of WBV exercise on contralateral strength training. Materials and Methods: Forty-two young adult healthy volunteers were randomized into two groups: WBV exercise and Sham control. An isometric semi-squat exercise during WBV was applied regularly through 20 sessions. WBV training was applied to the right leg in the WBV group and the left leg was isolated from vibration. Sham WBV was applied to the right leg of participants in the Control group. Pre- and post-training isokinetic torque and reflex latency of both quadricepses were evaluated. Results: The increase in the strength of right (vibrated) knee extensors was 9.4 ± 10.7% in the WBV group ( p = .001) and was 1.2 ± 6.6% in the Control group ( p = .724). The left (non-vibrated) extensorsvibrated) knee extensors w4 ± 8.4% in the WBV group ( p = .038), whereas it decreased by 1.4 ± 7.0% in the Control ( p = .294). The strength gains were significant between the two groups. WBV induced the reflex response of the quadriceps muscle in the vibrated ipsilateral leg and also in the non-vibrated contralateral leg, though with a definite delay. The WBV-induced muscle reflex (WBV-IMR) latency was 22.5 ± 7.7 ms for the vibrated leg and 39.3 ± 14.6 ms for the non-vibrated leg. Conclusions: Chronic WBV training has an effect of the cross-transfer of strength to contralateral homologous muscles. The WBV-induced muscular reflex may have a role in the mechanism of cross-transfer strength.